Miten yhdistetyn todellisuuden urheilusovelluksella voidaan vaikuttaa harjoittelun laatuun ja motivaatioon - Zwift - Granqvist, Niklas (2025)
The purpose of this master's thesis was to investigate how the mixed reality sports app Zwift supports the quality and motivation of training in triathlon. The aim of the study was to understand how the overall user experience of the application and its offered features, such as real-time data, gamification, and social interaction, affect users' experiences and training. Additionally, the study examined how users' individual needs, backgrounds, and experiences are reflected in the use of the application. The theoretical part of the study was conducted as a literature review, addressing augmented reality sports applications and self-determination theory. Data collection was conducted using qualitative methods, with a target group of 12 active Zwift users. The interviews were conducted using semi-structured thematic interviews, focusing on areas that were essential for the research. The data analysis was based on a theory-driven approach, with self-determination theory serving as the framework. The results showed that the Zwift app particularly supports users' autonomy by offering a wide range of exercise options and customization possibilities. The sense of competence was reinforced through real-time data and goal achievement, while the sense of relatedness was supported by group rides and virtual competitions. The role of gamification as a feature of the application also emerged as a significant factor in supporting motivation. The role of the physical environment and technological challenges also emerged as significant factors in terms of the application's user experience. In the conclusions, the study emphasizes how Zwift can serve as an effective tool when its features support users' psychological basic needs. The key features of the application are its versatile functionalities and personalization for users' individual needs.